Efektivitas Balai Latihan Kerja (BLK) Komunitas Dalam Meningkatkan Kualitas Tenaga Kerja Di Kota Blitar - Laksono, Wisnu (Universitas Nahdlatul Ulama Blitar, 2025)
This study was conducted with the aim of analyzing the effectiveness of the Vocational Training Center (BLK) in improving the quality of the workforce in Blitar City. The research method used was a qualitative approach with field research, enabling the researcher to gain an in-depth understanding of the actual conditions on the ground. Data collection techniques included interviews, observations, and documentation, which were then validated through triangulation of sources, techniques, and time to ensure the validity of the information obtained. Based on the research results, the existence of the VTC has proven to be quite effective in supporting the improvement of workforce competencies. This effectiveness is evident in the provision of adequate facilities and infrastructure, the readiness of organizers in designing training programs, and the quality of instructors who possess relevant skills and experience. With this support, training graduates are expected to be able to compete in the job market. However, BLK also faces several challenges that require further attention. These challenges include limited funding, suboptimal human resource management, coordination issues among relevant parties, and a weak training evaluation system. These factors pose challenges in maintaining the consistency and sustainability of the training programs conducted by BLK.